Cover Picture: Highly Twisted Conformation Thiopyrylium Photosensitizers for In Vivo Near Infrared‐II Imaging and Rapid Inactivation of Coronavirus (Angew. Chem. Int. Ed. 13/2023). Issue 13 (27th February 2023) - Liu, Yishen; Gu, Meijia; Ding, Qihang; Zhang, Zhiyun; Gong, Wanxia; Yuan, Yuncong; Miao, Xiaofei; Ma, Huili; Hong, Xuechuan; Hu, Wenbo; Xiao, Yuling
Abstract : The relationship between molecular configuration and charge transfer processes in near‐infrared‐II (NIR‐II) chromophores was studied, and subsequently instructed the engineering of an efficient NIR photosensitizer (PS), as reported by Wenbo Hu, Yuliang Xiao et al. in their Research Article (e202214875 ). The resulting NIR‐II PS not only enables NIR‐II image‐guided in vivo pulmonary coronavirus photo‐ablation but also demonstrates a facile approach for the development of NIR heavy‐atom‐free PSs.